Natural Area Weeds: Skunkvine (Paederia foetida) - Kenneth A. Langeland; R. K. Stocker; D. M. Brazis (EDIS)
Native to eastern and southern Asia, skunkvine is an invasive plant species introduced to the USDA Field Station near Brooksville before 1897. It has been included on the Florida Exotic Pest Plant Council List of Invasive Species as a Category I, defined as “species that are invading and disrupting native plant communities in Florida.” It was added to the Florida Noxious Weed List in 1999, making it illegal to possess, move, or release in Florida. This 3-page fact sheet was written by K. A. Langeland, R. K. Stocker, and D. M. Brazis, and published by the UF Department of Agronomy, February 2013.